PENERAPAN MODEL PEMBELAJARAN KOOPERATIF TIPE NUMBERED HEADS TOGETHER DALAM PROSES PEMBELAJARAN SISWA SEKOLAH DASAR - Fauzan, Ahmad (LPPM STKIP Pangeran Dharma Kusuma Segeran Juntinyuat Indramayu, 2023)
This study aims to find out how the application of the use of the Numbered Heads Together type of cooperative learning model to improve the learning process followed by the learning outcomes of Class IV students at SDN in Segeran Kidul Indramayu. The method applied is classroom action research (CAR) through Kemmis and Mc. Taggart’s model with three cycles. Each cycle includes planning, action, observation and reflection activities. The research instrument includes student and teacher observation sheets, 20-questions multiple choice test, and documentation. The data analysis includes data reduction, data presentation and conclusion drawing. The results showed the improvement in the learning process followed by significant learning outcomes. The improvement of the learning process in the first cycle is that the students reach the indicators of the learning process by 51%. The increase in the learning process in the second cycle was 69.38% with an increase of 18.38% from the first cycle. And in the third cycle, the students reach the learning process indicators of 84.5% with an increase of 15.12% from the second cycle. This is reinforced by the average value of the pre-test (46.73) with a percentage of completeness 0% smaller than the average value of the post-test (62.82) with a percentage of completeness of 21.73% in the first cycle. The percentage of student learning outcomes in the second cycle of 47.82% with an average value of 72.17. The increase is 26.09% from the learning outcomes in the first cycle; The percentage of learning outcomes in the third cycle was 82.60% with an average of 82.39. The increase is 34.78% from learning outcomes in the second cycle, and this has reached the indicator of success determined by the school through the KKM, which is 75%.